2020
DOI: 10.1101/2020.04.08.029785
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epigenetic landscape of pancreatic neuroendocrine tumours reveals distinct cells of origin and means of tumour progression

Abstract: 25Recent data suggest that Pancreatic Neuroendocrine Tumours (PanNETs) originate from α-or β-cells of 26 the islets of Langerhans. The majority of PanNETs are non-functional and do not express cell-type 27 specific hormones. We examined whether tumour DNA methylation (DNAme) profiling combined with 28 genomic data could identify cell of origin and reveal pathways involved in PanNET progression. We 29 analysed genome-wide DNAme data of 125 PanNETs and sorted α-and β-cells. To confirm cell identity, 30we investi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…The largest two groups, Groups A and B, clearly distinguished NECs from the rest of the cohort. Three recent studies have investigated PanNET subgroups at the epigenetic level [17][18][19] . Cejas et al looked at histone acetylation and transcriptomes 17 of NET samples, with two neuroendocrine samples both from the ileum.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The largest two groups, Groups A and B, clearly distinguished NECs from the rest of the cohort. Three recent studies have investigated PanNET subgroups at the epigenetic level [17][18][19] . Cejas et al looked at histone acetylation and transcriptomes 17 of NET samples, with two neuroendocrine samples both from the ileum.…”
Section: Discussionmentioning
confidence: 99%
“…Cejas et al looked at histone acetylation and transcriptomes 17 of NET samples, with two neuroendocrine samples both from the ileum. Di Domenico et al 18 and Lakis et al 19 used 450K methylation profiles from cohorts of well-differentiated PanNET samples. Our work expands the field by including the most aggressive subtypes of PanNENs: NETG3 and NEC tumors, which the aforementioned studies largely excluded (Di Domecio et al included only two NETG3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, at least two different progenitor cells can give rise to non-functional PanNETs, the α-cells lineage (ARX +) or β-cells lineage (PDX +) [19]. Global DNAme profiles of the early stage of PanNET show strong similarities with both α-and β-cell DNAme profiles, while late stage tumors show a lower degree of similarities with normal cell types [47]. An additional study confirmed that different molecular subtypes of PanNET arise from different cellular origins, or from mature β-cell lineage, or islet cell precursors [48].…”
Section: Genomic Features Shared Among Pdac Pannet and Pannecmentioning
confidence: 99%